2015
DOI: 10.1371/journal.pone.0143966
|View full text |Cite
|
Sign up to set email alerts
|

Newly Developed Sarcopenia as a Prognostic Factor for Survival in Patients who Underwent Liver Transplantation

Abstract: IntroductionThe relationship between a perioperative change in sarcopenic status and clinical outcome of liver transplantation (LT) is unknown. We investigated whether post-LT sarcopenia and changes in sarcopenic status were associated with the survival of patients.MethodThis retrospective study was based on a cohort of 145 patients from a single transplant center who during a mean of 1 year after LT underwent computed tomography imaging evaluation. The cross-sectional area of the psoas muscle of LT patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 36 publications
(42 reference statements)
7
70
0
Order By: Relevance
“…. A total of 38 articles (years 2010‐2018) were included, in which 92% (n = 35) were conducted in adults and 8% (n = 3) were conducted in pediatric populations …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…. A total of 38 articles (years 2010‐2018) were included, in which 92% (n = 35) were conducted in adults and 8% (n = 3) were conducted in pediatric populations …”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies (n = 29/35) focused on pre‐LT sarcopenia, which included studies that characterized patients with sarcopenia (n = 26), SO (n = 1) as well as both sarcopenia and SO (n = 2) . Five studies longitudinally tracked changes in pre‐LT sarcopenia into the post‐LT period (up to 19.3 months) . Only 1 article evaluated post‐LT SO .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, 15% who were preoperatively non-sarcopenic developed sarcopenia after liver transplantation (5). Several reports also suggested that muscle depletion has not recovered in the first year after liver transplant (14).…”
Section: Changes In Sarcopenic Status After Liver Transplantationmentioning
confidence: 99%
“…The state of sarcopenia rather worsen after liver transplantation. Jeon et al (5) reported that sarcopenia continued to be a risk factor for mortality even in patients who managed to survive their early posttransplant periods. Because sarcopenia continues, or rather worsens in some recipients, after liver transplantation, their vulnerability to infections, frailty syndrome in general, caused by sarcopenia should be seriously cautioned in addition to the problems relating to immunosuppressants.…”
Section: Changes In Sarcopenic Status After Liver Transplantationmentioning
confidence: 99%